(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The development of professional competence and creativity in preschool educators is essential for fostering high-quality early childhood education. Professional competence includes pedagogical knowledge, emotional intelligence, and curriculum planning, while creativity enhances engagement and innovation in teaching. This article explores strategies for nurturing these qualities, such as continuous professional development, technology integration, and institutional support. By fostering a dynamic and creative learning environment, educators can provide children with enriched educational experiences that promote cognitive and social development.